Students' Understanding of Historical Events: A Case Study of The 2017 Film Kartini - Armi Yarsi; Nuraedah Nuraedah; Mutawakkil Mutawakkil; Windayanti Windayanti (Journal of Educational Sciences, 2026)
History education helps students understand past events and develop historical awareness. However, history is often considered less interesting when taught only through textbooks. Therefore, films can be used as alternative learning media to present historical events in a more engaging and meaningful way. One example is Kartini (2017), which portrays the struggle of R.A. Kartini for women’s education and emancipation in Indonesia. This study aims to identify students’ understanding of historical events through the film Kartini (2017) and examine the use of film as a learning medium in history education. The study focuses on analyzing students’ responses to case-study questions and assessing their understanding based on Bloom’s cognitive indicators of comprehension: expressing, interpreting, and classifying information. A mixed-methods approach with a convergent design was employed involving twelfth-grade students at SMAN 5 Palu. Data were collected through case-study questions and analyzed qualitatively and quantitatively. The average score for expressing information was 78.18%, while interpreting and classifying information reached 90.63% and 90.00%, respectively. These results suggest that the film Kartini (2017) effectively supports students’ understanding of historical events and can serve as a valuable learning medium in history education.